PENGARUH AKTIVITAS DAN PROFITABILITAS TERHADAP RETURN SAHAM PADA SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Syifa Nurpalah, - (2020)
Syifa Nurpalah, 1602187. Effect of Activity and Profitability to Stock Return of Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange 2014-2018 period. Under the guidance of Budhi Gautama, S.E., M. Sc and Netti Siska Nurhayati, S.E., MM. The research based on the decreased of stock returns in Consumer goods industry sector in the 2014-2018 period. This study aims to visualizing of activity with Inventory Turnover (ITO) indicators, visualizing the Profitability with Return on Assets (ROA) indicators and visualizing of Stock Returns, and to determine the effect of Activities and Profitability on Stock Returns. This research is using descriptive and verification methods using hypothesis testing. The analytical tools used include panel data regression analysis, regression significance test and regression coefficient significance tests. The data used secondary activity data, Profitability and Stock Return sourced from the company's financial statement data and ICMD for the 2014-2018 period. The study population consisted of 36 companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample data used in this study were 33 companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange in the 2014-2018 period using purposive sampling techniques. The results of this study illustrate that activity, profitability and stock returns tend to decrease, especially in the last two years. Based on the results of the analysis of the activity test and profitability has a positive effect on stock returns in the consumer goods industry sector in the 2014-2018 period. Recommendations for the consumer goods industry sector to increase sales, manage inventory management properly, increase profits and streamline costs in order to increase stock prices and stock returns. Keywords: Activity, Profitability, Stock Return